We have "\\frac{dx}{-x(x+y)} = \\frac{dy}{y(x+y)} = \\frac{dz}{(x-y)(2x+2y+z)}" ______________(1)
Now from first two part of equation (1),
"\\frac{dx}{-x(x+y)} = \\frac{dy}{y(x+y)}"
"\\implies \\frac{dx}{-x} = \\frac{dy}{y}"
Now by integration, we get "-\\ln(x) = \\ln(y) - \\ln(c_1) \\implies c_1 = xy" ________(2)
Now also "\\frac{dx}{-x(x+y)} = \\frac{dy}{y(x+y)} = \\frac{dz}{(x-y)(2x+2y+z)} = \\frac{2dx+2dy+dz}{(x-y)z}"
"\\implies \\frac{dz}{(x-y)(2x+2y+z)} = \\frac{2dx+2dy+dz}{(x-y)z}"
"\\implies \\frac{dz}{2x+2y+z} = \\frac{2dx+2dy+dz}{z}"
"\\implies zdz = (2x+2y+z) (2dx+2dy+dz)"
Hence by integration, we get
"\\frac{z^2}{2} = \\frac{(2x+y+z)^2}{2} + \\frac{c_2}{2}"
"\\implies c_2 = z^2- (2x+y+z)^2" ______________(3)
Hence, solution is :
"c_2 = f(c_1)"
"\\implies z^2- (2x+y+z)^2 = f(xy)" .
Comments
Leave a comment